(untitled) (New York, 2000)
Two financial planners present stories of 31 real investors, each at a different phase in his or her life and each facing different financial challenges. Investors profiled use an approach advocated by the authors, which involves thinking of investments and wealth goals as a "virtual business" with the investor as the CEO and a professional investment advisor as Chief Operating Officer. Material is intended to help advisors work with their clients and to help investors take control of their investment planning and select an advisor.
Keywords: Finance, personal,Retirement income,Estate planning; Planning